2008
DOI: 10.1111/j.1440-1770.2008.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Sediment phosphorus characteristics in the clearwater state of Lake Mogan, Turkey

Abstract: This study examined the vertical distributions of total phosphorus (TP) and phosphorus fractions, and the iron and organic matter, in the littoral sediment in a macrophyte-dominated, clearwater state in Lake Mogan between September 2005 and August 2006. Benthic macroinvertebrates and total bacteria in the sediment also were determined. No clear seasonal or depth-related (0-20 cm) patterns were found in sediment concentrations for the measured parameters. The phosphorus release was quantitatively very low, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
1
15
1
Order By: Relevance
“…The reservoir sediment phosphorus fractions exhibited a majority of inorg-P fractions, consistent with the results reported by the authors Pulatsu et al (2008) and Søndergaard et al (1996). Org-P in this study was measured to be 24.1% of the TP fractions in the month of June 2008.…”
Section: Sampling Locationssupporting
confidence: 89%
“…The reservoir sediment phosphorus fractions exhibited a majority of inorg-P fractions, consistent with the results reported by the authors Pulatsu et al (2008) and Søndergaard et al (1996). Org-P in this study was measured to be 24.1% of the TP fractions in the month of June 2008.…”
Section: Sampling Locationssupporting
confidence: 89%
“…The authors also found a significant correlation between sediment TC and TP concentrations in the vertical profiles, as observed in Peri Lake. Pulatsu et al (2008) found that bacteria in oxic sediments can retain P, what could also have happened in the top layers of Peri cores, resulting in the higher TP content observed, especially in core P1. According to Fontes et al (2013), bacterial community plays an important role in the metabolism of Peri Lake and, thus, influence nutrient dynamics and record in the sediments.…”
Section: Resultsmentioning
confidence: 87%
“…Besides recreational use, Lake Mogan has been identified as an important water bird area and has had protected status since 1990. A study of phosphorus release from the littoral sediment showed that the external phosphorus load must be reduced to control the eutrophication (Pulatsü et al, 2009).…”
Section: Study Sitementioning
confidence: 99%